2023
DOI: 10.1002/ohn.530
|View full text |Cite
|
Sign up to set email alerts
|

Stellate Ganglion Block for the Treatment of COVID‐19‐Induced Olfactory Dysfunction: A Prospective Pilot Study

Andrew M. Peterson,
Brevin J. Miller,
Dorina Kallogjeri
et al.

Abstract: ObjectiveThe objective of this study was to explore the safety and feasibility of stellate ganglion blocks (SGBs) to treat persistent COVID‐19‐induced olfactory dysfunction (OD). Secondarily, the goal was to determine effect sizes to plan a future randomized clinical trial.Study DesignProspective case series.SettingQuaternary Care Academic Medical Center.MethodsIn this single‐arm pilot trial, adult participants with a COVID‐19 diagnosis ≥ 12 months prior to enrollment with OD underwent bilateral SGBs. Subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…However, they did not report if overall changes in the UPSIT scores or parosmia severity scores were statistically significant. 33 In this current study, interestingly, while SGB demonstrated a significant impact on subjective parosmia severity and QOL metrics, there was no significant improvement in odor identification from pre-to post-SGB as measured through the BSIT for the overall, UL, and BL cohorts (Table 3). Additionally, in the comparison of the overall SGB cohort to the general COVID-19 OD cohort, patients undergoing SGB presented clinically with significantly higher baseline BSIT scores than patients with COVID-19 OD (Table 2).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, they did not report if overall changes in the UPSIT scores or parosmia severity scores were statistically significant. 33 In this current study, interestingly, while SGB demonstrated a significant impact on subjective parosmia severity and QOL metrics, there was no significant improvement in odor identification from pre-to post-SGB as measured through the BSIT for the overall, UL, and BL cohorts (Table 3). Additionally, in the comparison of the overall SGB cohort to the general COVID-19 OD cohort, patients undergoing SGB presented clinically with significantly higher baseline BSIT scores than patients with COVID-19 OD (Table 2).…”
Section: Discussionmentioning
confidence: 57%
“…One study of 20 participants undergoing BL SGB found that at 1 month after treatment, 55% of patients achieved a clinically meaningful improvement of 4 points or greater on the University of Pennsylvania Smell Identification Test (UPSIT), an objective olfactory function test, and 50% reported improvement in parosmia. However, they did not report if overall changes in the UPSIT scores or parosmia severity scores were statistically significant 33 …”
Section: Discussionmentioning
confidence: 99%
“…To the Editor, Duckett et al deserve admiration for their comprehensive meta-analysis and systemic review of the prevalence of postoperative radiotherapy (PORT) delay and assessment of variations among care delivery settings in head and neck cancer (HNC) patients. 1 The present systematic review comprised 36 studies, while the metaanalysis covered 14 studies. The meta-analysis revealed that nearly half of patients (48.6%) underwent PORT after a lapse of >6 weeks following surgery.…”
Section: Author Contributionsmentioning
confidence: 99%
“…Reply to "A Review of Stellate Ganglion Block for the Treatment of COVID-19-Induced Olfactory Dysfunction" DOI: 10.1002/ohn.700 Thank you to Youssef et al for your commentary regarding our manuscript titled, "Stellate Ganglion Block for the Treatment of COVID-19-Induced Olfactory Dysfunction: A Prospective Pilot Study." 1 We appreciate your review of our study and would like to offer further information on some of the points raised in the commentary.…”
mentioning
confidence: 96%
“…We read with pleasure the article by Peterson et al, 1 titled "Stellate Ganglion Block for the Treatment of COVID-19-Induced Olfactory Dysfunction: A Prospective Pilot Study." We offer additional commentary on the extrapolated conclusions and hope these perspectives may provide insight into areas that may require further research.…”
mentioning
confidence: 99%